Thanksgiving service for the life of Dr. Kenneth Earle William Whitbourne.
This funeral programme was done for Dr. Kenneth Earle William Whitbourne. The funeral service took place on Friday, May 21, 1993, at the University Chapel Mona Campus.
Keywords: Programme. -- Jamaica